Personal Growth and Wellbeing: An Iterative Mindset Assessment and Perspective - Kyra Bobinet; Jeni L. Burnette; Whitney Becker; Mallory Rowell (Behavioral Sciences, 2025)
Interest in personal growth is expanding in both the popular press and the scientific literature. These expansions incorporate varied theoretical approaches and multiple areas of life. In the current work, we propose a novel perspective that focuses on managing failure to reach self-improvement goals and improving wellbeing. Specifically, we introduce an iterative mindset, which is the belief that making adaptations combined with deliberate practice and neutralizing of failure is critical for lasting transformations. We seek to contribute to the personal growth and mindset literature in two key ways. First, we developed and validated a new measure, called an Iterative Mindset Inventory (IMI), examining factor structure, reliability, and validity. Second, we investigated the links between iterative mindsets, self-improvement, and wellbeing, extending existing work on the power of beliefs to shape self-development. In both studies (Study 1, N = 871; Study 2, N = 345), we incorporated online samples that resembled the adult population of the United States. In Study 1, we found evidence for the proposed theoretical three-factor structure of an iterative mindset, which we label iterate, practice, and assess. In Study 2, using a longitudinal approach across three weeks, we confirmed the three-factor structure and found high test–retest reliability. Iterative mindsets were also positively linked to weight-loss success across both studies and to self-efficacy and wellbeing in Study 2.